(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
According to certain theories, yoga poses have an impact on both human physiology andpsychology. Several studies have been conducted on the subject of sports, especially in swimming andshort distance athletics. In this study, we will evaluate how yoga poses impact the development ofshoulder and leg strength as well as the psychological system (age, height, and weight). The resultindictes that yoga poses enhance both game performances. Regular yoga practice helps most playersincrease their stamina and reduce their performance times in comparison to the pre-test. This studyattempts to look into how a specific yoga pose influences in swimmers and short distance athletes .